What explains the structuring of fish assemblages in the upper Parana river basin, Mato Grosso do Sul? - Renner Fernando da Silva Córdova Junior (2024)
This study investigates the species richness and composition of fish assemblages in the upper Paraná River basin. I correlated species richness and distribution with regional factors, such as the position of sub-basins and the connectivity between ottobasins, and local factors, such as the physicochemical characteristics of water and land cover as an anthropogenic influence on the areas collected. To further explore the interplay among these factors and their impact on assemblage richness and composition, i divided my study into two chapters. In the first chapter, I investigated the local (LCBD) and specific (SCBD) contribution to beta diversity. I evaluated 275 sites in low-flow streams (